Reciprocal change of occipitocervical parameters after anterior cervical discectomy and fusion - Park, Eugene J. (Sci Rep, 2021)
To evaluate the reciprocal changes in occipitocervical parameters according to the recovery of cervical lordosis (CL) after anterior cervical discectomy and fusion (ACDF) in patients with sagittal imbalance. Sixty-five cases that underwent ACDF were followed. They were divided according to the recovery of the CL: Group 1 (ΔCL > 5°, 30 cases) and Group 2 (ΔCL < 5°, 35 cases). The following parameters were measured: occiput-cervical inclination (OCI), CL, occiput-C2 angle (OC2A), distance between external occipital protuberance and spinous process of C2 (OC2D), distance between spinous processes of C2 and C7 (C27D), and shortest distance between the plumb line of C2 body and posterosuperior corner of C7 (C27SVA). Overall, all parameters changed significantly after ACDF. Preoperative CL and preoperative C27D showed a correlation with ΔCL. ΔCL was negatively correlated with ΔC27D and ΔC27SVA. In Group 1, CL increased from − 2.60 ± 1.88° to 11.57 ± 1.83°, OC2A decreased from 23.96 ± 2.05° to 19.87 ± 1.36°, OC2D increased from 82.96 ± 1.48 mm to 86.50 ± 1.81 mm, C27D decreased from 95.61 ± 2.66 mm to 87.01 ± 2.50 mm, and C27SVA decreased from 24.14 ± 2.20 mm to 17.06 ± 2.14 mm. In Group 2, only OCI decreased significantly after ACDF. ACDF can increase CL postoperatively in patients with cervical sagittal imbalance. Patients with significant CL recovery after ACDF showed a reciprocal change in occipitocervical parameters. (OC2A, OC2D).